Indonesia's Violence against Children: The Challenges of Using the Best Interest Principle in Court Decisions - Sholehudin, Miftahus; Maharani, Syaputri (PT. Riset Press International, 2025)
Incest cases in Indonesia remain a concerning issue that demands serious attention from various stakeholders. This study is motivated by legal challenges regarding the protection of incest victims, particularly with the application of the best interest of the child principle. In practice, however, cases of violence against children are often not addressed with an approach that prioritizes the best interest of the child. This research focuses on analyzing Verdict No. 148/Pid.Sus/2023/PN.BLN aims to identify the extent to which judicial considerations in resolving this case have either disregarded or adhered to the best interest of the child principle. The research adopts a normative legal method involving analysis, observation, and examination of written legal materials. In normative legal research, the focus lies on applying existing laws as a guiding framework within societal life, determining what is considered appropriate. This study employs a case-based approach by analyzing primary and secondary legal materials, including legislation, court decisions, and relevant legal literature. Data were collected through a literature review and analyzed deductively to address the research questions. The findings indicate that in Verdict No. 148/Pid.Sus/2023/PN.BLN, the judges have not fully prioritized the best interest of the child principal. Although efforts were made to protect children who are victims of incest, several critical aspects were not adequately considered. This highlights the need to enhance judges' awareness and understanding of the importance of the best interest of the child principle in every decision involving victims of violence, particularly in cases of incest.